A Comparative Study of Effect of Various Sansevieria Thunb. Leaf Extracts on the Lipid Peroxidation in the Equine Erythrocyte Suspension - Tkachenko, Halyna; Buyun, Lyudmyla; Maryniuk, Myroslava; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
In this study, we continued our investigations concerning the interaction of leaf extracts obtained from various Sansevieria species with the equine erythrocytes. The purpose of the present study was to compare the in vitro effect of buffer extracts obtained from leaves of various species from Sansevieria genus against lipid peroxidation in equine erythrocytes. The succulent leaves of living Sansevieria plants were sampled for the study. The results of the study showed that the leaves of S. francisii and S. forskaliana led to a non-significantly decrease of 2-thiobarbituric acid reactive substances (TBARS) concentration in erythrocytes. However, S. hyacinthoides and S. cylindrica had a significant increase of TBARS level in the extract-treated erythrocytes (by 29.7 and 21 %, p<0.05, respectively). The outcome of this study suggests that Sansevieria species has a promising antioxidant and prooxidant potential. Further studies involving bioassay-guided identification of the main compounds in plants is necessary to affirm and maximize the possible use of the plant as a therapeutic remedy for prevention of lipid peroxidation in erythrocytes. The antioxidative and prooxidative mechanism of various Sansevieria species in equine erythrocyte suspension will be further studied in detail. The obtained information may be useful in the clinical usage of plants in medicine and veterinary.